Revolución y fiscalidad municipal. La Hacienda de la Villa de Madrid en el reinado de Fernando VII - MARTINEZ-NEIRA, MANUEL (Historia del Derecho, 2022)
The municipal treasury is taken here as a point of observation for reflecting on the changes that took place in the transition from the Ancien Régime (where rights are declined from the corporation) to the liberal one (where rights are declined from the individual). For this reason, the framework of the reign of Fernando VII and the Villa de Madrid are suitable chronological and spatial spaces for this research, which is of interest to the cultivators of institutional history and to those dedicated to local history.